2015
DOI: 10.7287/peerj.preprints.811v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Morphological diversity in tenrecs (Afrosoricida, Tenrecidae): comparing tenrec skull diversity to their closest relatives

Abstract: Morphological diversity is often studied qualitatively. However, to truly understand the evolution of exceptional diversity, it is important to take a quantitative approach instead of relying on subjective, qualitative assessments. Here, we present a quantitative analysis of morphological diversity in a Family of small mammals, the tenrecs (Afrosoricida, Tenrecidae). Tenrecs are often cited as an example of an exceptionally morphologically diverse group. However, this assumption has not been tested quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Tenrec skulls are less morphologically diverse than those of golden moles. It is suggested that the similarities in skull morphology among the speciose genus Microgale masks morphological diversity among the rest of the family [ 111 ] Hyracoidea All four extant hyrax species have short skulls and deep dentary bones. The skull has a postorbital bar, which is sometime complete ( Dendrohyrax ) and sometime incomplete ( Heterohyrax and Procavia ) None Proboscidea All extant elephant species (Loxodonta and Elephas ) have short, tall skulls which are pneumatized particularly in the cranial roof, thereby reducing cranium weight.…”
Section: Morphological Diversity In Mammalian Facesmentioning
confidence: 99%
“…Tenrec skulls are less morphologically diverse than those of golden moles. It is suggested that the similarities in skull morphology among the speciose genus Microgale masks morphological diversity among the rest of the family [ 111 ] Hyracoidea All four extant hyrax species have short skulls and deep dentary bones. The skull has a postorbital bar, which is sometime complete ( Dendrohyrax ) and sometime incomplete ( Heterohyrax and Procavia ) None Proboscidea All extant elephant species (Loxodonta and Elephas ) have short, tall skulls which are pneumatized particularly in the cranial roof, thereby reducing cranium weight.…”
Section: Morphological Diversity In Mammalian Facesmentioning
confidence: 99%